Habanadigital: a smart city project adapted to Cuban conditions - Pina Amargos, Joaquin Danilo (2024)
One of the sustainable development goals established by the United Nations in the 2030 Agenda is to make cities and human settlements inclusive, safe, resilient and sustainable. The Smart City concept is aimed in this direction and one of the requirements considered by most current solutions is the intensive use of modern technologies to increase efficiency in order to better use available resources. However, in countries with technological limitations due to their underdevelopment or because they are under sanctions from foreign powers, this requirement cannot be achieved in the short term. This paper presents a novel solution through a local development project that involves civil organizations, the different economic actors, the government and the community so that in an orderly way it manages to solve the existing problems at the local level and the best solutions are generalized in the rest of the province. The proposal is made in the context of the province of Havana Cuba but can be adapted for extension to other provinces of the country and even in other geographical areas that have the stated limitations.